âTINJAUAN PELAKSANAAN PERATURAN WALIKOTA YOGYAKARTA NOMOR 79 TAHUN 2010 TENTANG PEMBATASAN USAHA WARALABA MINIMARKET DI KOTA YOGYAKARTA - , DEWI PERTIWI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to determine the implementation of the Mayor of Yogyakarta Regulation No. 79 Year 2010 on the restriction of the franchise minimarket City Yogyakartadan role of the Licensing Agency of Yogyakarta, Yogyakarta and Disperindagkoptan Commission in protecting small businesses. Because there are quite a lot of Yogyakarta city mini franchise. Of course, if allowed to compete for granted, then the small entrepreneur will not be able to compete with the existence of mini-franchise. Because small businesses have lost capital in terms of business management and also management. This research is descriptive qualitative. Data collection was conducted by means of interviews with informants and respondents. Then do the data processing and related primarily associated with regulation of Yogyakarta Mayor Regulation No. 79 Year 2010. In order to protect small businesses make the City Government of Yogyakarta Yogyakarta Mayor Regulation No. 79 Year 2010. Within this regulation there are rules regarding the maximum amount allowed minimarket franchise that is 52 units. It also regulates the allowed path anywhere that there are 41 roads. There are some differences in the implementation of the regulations and their implementation in which the maximum quota for each district. However, in this case because the minimarket franchise feet before the existence of this rule. Therefore, it will be given 1 time renewal period and after that have to adjust. The role of the Licensing Agency of Yogyakarta in sustaining small businesses was limited to the exemption or reduction of the cost of local tax for SMEs. while the role of Yogyakarta Disperindagkoptan provide oversight and guidance to the franchise in order to partner with mini SMEs, as well as to small businesses to manage their business better. Commission in protecting small businesses or traditional market is limited to the provision of letters of advice and judgment to the government and supervision of business competition. However, the Commission's role directly to the city of Yogyakarta is currently no. But for some other areas the Commission has several times giving letters of advice and judgment, and once also gave verdict against Indomaret to stop its expansion.